Concrete Damaged Plasticity (CDP) adjustment parameters for the application in simulations of timber or wood composite structures - Christoforo, André Luis; Arroyo, Felipe Nascimento; Dantas De Sousa, Alex Micael [UNESP]; Mascarenhas, Fernando Junior Resende; Panzera, Tulio Hallak; Lahr, Francisco Antonio Rocco; Geraldes Dias, Alfredo Manuel Pereira (Elsevier, 2025)
Simulations of wooden structures and mixed wooden and concrete structures in fire situations are complex to develop due to the lack of a specific constitutive model that directly correlates the temperature and strength of wood. This limitation has been overcome with the use of CDP (Concrete Damaged Plasticity). Although the CDP parameters used for wood simulation have been the same as those considered in concrete simulation, this adoption can lead to inaccuracy in estimating the structure's failure load and its mechanical performance. Therefore, this study proposes to determine the most appropriate combination of CDP parameters for simulating wood and timber structures. With variations in the expansion angle (θ), the ratio between biaxial and uniaxial strength (fb0/fc0), the shape factor K, and viscosity (μ), 108 non-linear simulations were carried out. The results indicated that the combined values of the parameters θ = 5°, fb0/fc0 = 0.70, K = 0.50, and μ = 0.05, respectively, resulted in more accurate predictions about the structural behavior of Marupá wood (Simarouba amara Aubl.) under static bending, with an associated error of only 8.49 % in predicting breaking force. On the other hand, using the CDP parameters calibrated for concrete, the error in predicting the test's breaking strength was greater than 50 %. These results highlight the need for studies to establish the range of CDP parameter values in order to simulate the behavior of different wood species with greater precision.
Keywords: Concrete damaged plasticity; Marupá wood; Mechanical analysis; Numerical simulation; Parameter sensitivity analysis